KEABSAHAN PERJANJIAN SEWA RAHIM DALAM PERSPEKTIF HUKUM PERDATA DAN HUKUM ISLAM - Riyano Ihsya (2024)
This research aims to analyze the validity of surrogacy agreements from the perspectives of civil law and Islamic law. The practice of surrogacy agreements has garnered increasing attention globally and nationally; however, there remains ambiguity regarding the legal foundations and regulations governing it within the Indonesian legal framework. The enforcement of surrogacy agreements in civil law and Islamic law requires careful consideration to safeguard the rights of involved parties. This research employs a normative juridical approach by analyzing legal provisions (Statute Approach) and a conceptual approach. The findings indicate that, within the context of civil law, surrogacy agreements reside in a legal gray area. Nevertheless, concerning whether to permit or prohibit surrogacy agreements, Indonesian Civil Law leans more toward prohibition, while Islamic Law outright prohibits such agreements. Keywords: Surrogacy agreements, civil law, Islamic law